Causes of nephrotic syndrome in Sweden: The relevance of clinical presentation and demographics - Jönsson, Anneli; Hellmark, Thomas; Segelmark, Mårten; Forsberg, Anna; Dreja, Karl (Frontiers in Nephrology, 2023)
Background: Many different pathological processes can affect the integrity of the glomerular capillary wall and cause massive leakage of protein resulting in the Nephrotic Syndrome (NS). The prognosis and response to therapy is highly dependent on the cause of the NS. Clinical parameters such as age, influence what diagnosis is most likely. We examine the correlation between clinical parameters, and histologic diagnosis. Methods: Age, gender, haematuria, proteinuria, plasma creatinine, plasma albumin and final diagnosis were retrieved for all adult patients with NS as indication for biopsy and/or massive albuminuria in conjunction with a low plasma albumin from the biopsy module of the Swedish Renal Registry (SRR) between 2014 and 2019. A basic calculator was developed to demonstrate the importance of clinical presentations in relation to the likelihood of having a specific diagnosis. Results: 913 unique patients were included in the study. Overall membranous nephropathy (17%) was the most common diagnosis, but when studying those <50 years old or women, minimal change nephropathy (21 and 17 %) was the most frequent diagnosis. When examining either those between 50 and 70 years-old, those with chronic kidney disease (CKD) 4 or those with negative dipstick tests for haematuria diabetic nephropathy (23, 30 and 21 %) was the most common underlying disease. Among those with high grade haematuria (grade 3-4 on dipsticks) Membranoproliferative glomerulonephritis was most common (14%), closely followed by IgA nephropathy (13%). Focal segmental glomerulosclerosis (9.7%) was less common than in many comparable studies. Conclusion: Clinical parameters have a profound impact on the likelihood of different diagnoses in adult patients with NS. Differences in clinical practice, inclusion criteria in studies and probably genetic background are important to account for when comparing data from different parts of the world.